Extrafollicular Dermal Melanocyte Stem Cells and Melanoma - Hoerter, James D. (Hindawi Publishing Corporation, 2012)
Recent studies suggest that extrafollicular dermal melanocyte stem cells (MSCs) persist after birth in the superficial nerve sheath of peripheral nerves and give rise to migratory melanocyte precursors when replacements for epidermal melanocytes are needed on the basal epidermal layer of the skin. If a damaged MSC or melanocyte precursor can be shown to be the primary origin of melanoma, targeted identification and eradication of it by antibody-based therapies will be the best method to treat melanoma and a very effective way to prevent its recurrence. Transcription factors and signaling pathways involved in MSC self-renewal, expansion and differentiation are reviewed. A model is presented to show how the detrimental effects of long-term UVA/UVB radiation on DNA and repair mechanisms in MSCs convert them to melanoma stem cells. Zebrafish have many advantages for investigating the role of MSCs in the development of melanoma. The signaling pathways regulating the development of MSCs in zebrafish are very similar to those found in humans and mice. The ability to easily manipulate the MSC population makes zebrafish an excellent model for studying how damage to MSCs may lead to melanoma.